Learning Alternative Access Approaches for Transcatheter Aortic Valve Replacement: Implications for New Transcatheter Aortic Valve Replacement Centers - Henn, Matthew C. (Ann Thorac Surg, 2016)
BACKGROUND. Smaller transcatheter aortic valve replacement (TAVR) delivery systems have increased the number of patients eligible for transfemoral procedures while decreasing the need for transaortic (TAo) or transapical (TA) access. As a result, newer TAVR centers are likely to have less exposure to these alternative access techniques, making it harder to achieve proficiency. The purpose of this study was to evaluate the learning curve for TAVR approaches and compare perioperative outcomes. METHODS. From January 2008 to December 2014, 400 patients underwent TAVR (transfemoral, n = 179; TA, n = 120; and TAo, n = 101)). Learning curves were constructed using metrics of contrast utilization, procedural, and fluoroscopy times. Outcomes during the learning curve were compared with after proficiency was achieved. RESULTS. Depending on the metric, learning curves for all three routes differed slightly but all demonstrated proficiency by the 50th case. There were no significant differences in procedural times whereas improvements in contrast use were most notable for TA (69 ± 40 mL versus 50 ± 23 mL, p = 0.002). For both TA and TAo, fewer patients received transfusions once proficiency was reached (62% versus 34%, p = 0.003, and 42% versus 14%, p = 0.002, respectively). No differences in 30-day or 1-year mortality were seen before or after proficiency was reached for any approach. CONCLUSIONS. The learning curves for TA and TAo are distinct but technical proficiency begins to develop by 25 cases and becomes complete by 50 cases for both approaches. Given the relatively low volume of alternative access, achieving technical proficiency may take significant time. However, technical proficiency had no effect on 30-day or 1-year mortality for any access approach.